ICC 2021 - IEEE International Conference on Communications 2021
DOI: 10.1109/icc42927.2021.9500663
|View full text |Cite
|
Sign up to set email alerts
|

Near-field Localization with a Reconfigurable Intelligent Surface Acting as Lens

Abstract: Exploiting wavefront curvature enables localization with limited infrastructure and hardware complexity. With the introduction of reconfigurable intelligent surfaces (RISs), new opportunities arise, in particular when the RIS is functioning as a lens receiver. We investigate the localization of a transmitter using a RIS-based lens in close proximity to a single receive antenna element attached to reception radio frequency chain. We perform a Fisher information analysis, evaluate the impact of different lens co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 25 publications
0
79
0
Order By: Relevance
“…For the receiver mode, an RIS can be configured with a nearly continuous phase profile, acting as a lens. Due to the large size of the RIS, wavefront curvature can be harnessed to localize MS and help with system synchronization [14]. For the transmitter mode, an RIS can act similarly to analog transmit beamformer and generate phase-shift keying (PSK) modulated symbols as pilots, hence the channel and position estimation can be performed.…”
Section: B Ris For Localizationmentioning
confidence: 99%
“…For the receiver mode, an RIS can be configured with a nearly continuous phase profile, acting as a lens. Due to the large size of the RIS, wavefront curvature can be harnessed to localize MS and help with system synchronization [14]. For the transmitter mode, an RIS can act similarly to analog transmit beamformer and generate phase-shift keying (PSK) modulated symbols as pilots, hence the channel and position estimation can be performed.…”
Section: B Ris For Localizationmentioning
confidence: 99%
“…The wireless environment is assumed to also include passive objects contributing to multipath signal reflection. [8], at the UE side [12], or as a separate reflector [13], [14]), wireless settings (multiple-input multiple-output (MIMO) [14], [15], multiple-input single-output (MISO) [10], and singleinput single-output (SISO) [9], [11]), etc. Furthermore, RISs can be used to assist the radar systems to improve the target detection capabilities [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…For the same scenario, the effects of limited RIS phase resolution was investigated in [18]. In [8], localization with an RIS acting as a lens has been considered and an estimation algorithm was proposed. Nearfield localization with one BS and an RIS has been studied in [6], [9], where it is shown that the wavefront curvature can be used to localize the UE, even if the direct path from the BS to UE is blocked.…”
Section: Introductionmentioning
confidence: 99%
“…They can support a wide variety of electromagnetic functionalities [8], ranging from perfect and controllable absorption, beam and wavefront shaping to polarization control, broadband pulse delay, radio-coverage extension, and harmonic generation. The RIS technology is envisioned to coat objects in the wireless environment [2] (e.g., building facades and room walls), and can operate either as a reconfigurable beyond Snell's law reflector [1], or as an analog receiver [9] or lens [10] when equipped with a single Radio-Frequency (RF) chain, or as a transceiver with multiple relevant RF chains [11].…”
Section: Introductionmentioning
confidence: 99%